Factors Influencing the Competence of Indonesian Migrant Workers in Japan’s Food Processing Industry - Rismaja Putra (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Rising demand in Japan’s food processing industry underscores the importance of Indonesian migrant workers’ technical and non-technical competencies. This study aims to analyze the influence of training received, education, Japanese language proficiency, skills, work experience, and level of cultural adaptation on the competence of Indonesian migrant workers in the food processing industry in Japan. This study employed a mixed-methods approach, combining quantitative questionnaires administered to 150 respondents with qualitative semi-structured interviews, in order to provide a comprehensive understanding of Indonesian migrant workers’ competencies in Japan. The findings indicate that language proficiency, skills, cultural adaptation, training, work experience, and education positively affect the competence of Indonesian migrant workers in Japan’s food processing industry. The importance of technical skills for operating machinery and maintaining quality, as well as non-technical skills like discipline, communication, and teamwork. Challenges such as language barriers, strict procedures, and cultural differences emphasize the need for pre-departure preparation and continuous training. Together, these factors strengthen both technical and non-technical competencies, supporting effective performance and high-quality production. The findings indicate that training, work experience, education, language ability, skills, and cultural adaptation can improve the competence of migrant workers in the food processing industry in Japan.